The Influence of Environmental, Social & Governance (ESG) Risk Rating on Debt Financing in Companies Listed on IDX ESG Leaders - Ria Mairosa; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study analyzes the impact of Environmental, Social & Governance (ESG) Risk Rating on Debt Financing in companies listed on IDX ESG Leaders for the period 2020-2023. Data was obtained through saturated sampling techniques and used an unbalanced panel with 30 companies included in IDX ESG Leaders for each period over the 3-year observation period, resulting in a total of 90 samples. The variables studied include ESG Risk Rating, Leverage, and Profitability. The results show that ESG Risk Rating has a significantly negative impact on Debt Financing. Control variables such as leverage do not impact Debt Financing, whereas profitability has a significantly negative impact on Debt Financing.